2012
DOI: 10.1051/0004-6361/201117809
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing exoplanet transit searches around low-mass stars with inclination constraints

Abstract: Aims. We investigate a method to increase the efficiency of a targeted exoplanet search with the transit technique by preselecting a subset of candidates from large catalogs of stars. Assuming spin-orbit alignment, this can be achieved by considering stars that have a higher probability to be oriented nearly equator-on (inclination close to 90 • ). Methods. We used activity-rotation velocity relations for low-mass stars with a convective envelope to study the dependence of the position in the activity-v sin i … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 68 publications
(76 reference statements)
1
12
0
Order By: Relevance
“…As expected, the K values are well below that required of the RV data presented in this work, but may be feasible with developing facilities (Fischer et al 2016). Additionally, the work of Herrero et al (2012) showed that Beta CVn has a relatively high probability that the inclination of the equatorial plane is > 80°relative to the plane of the sky (see Section 3.1), and so the transit probabilities are likely underestimated.…”
Section: Potential For Terrestrial Planetssupporting
confidence: 48%
See 1 more Smart Citation
“…As expected, the K values are well below that required of the RV data presented in this work, but may be feasible with developing facilities (Fischer et al 2016). Additionally, the work of Herrero et al (2012) showed that Beta CVn has a relatively high probability that the inclination of the equatorial plane is > 80°relative to the plane of the sky (see Section 3.1), and so the transit probabilities are likely underestimated.…”
Section: Potential For Terrestrial Planetssupporting
confidence: 48%
“…Given the quiet nature of the star, the question arises as to the stellar equatorial plane relative to the plane of the sky since this will influence the detectability of planetary signatures, assuming those orbits are coplanar with the stellar equator. In order to optimize blind transit searches, Herrero et al (2012) provided a catalog of stars whose inclination of the equatorial plane is likely > 80°relative to the plane of the sky. They adopt a rotational velocity of = v i sin 2.9 km s −1 and activity index of ¢ = -R log 4.885 HK ( ) for Beta CVn, and their methodology predicts a high probability (50% larger than the average of their sample) of the star having an inclination >  80 .…”
Section: Stellar Properties and Habitable Zonementioning
confidence: 99%
“…There are not many studies of HIP 114328 in the literature, only two papers are reported by SIMBAD, one on stellar activity (Jenkins et al 2011) and the other one on a list of candidates for targeted transit searches (Herrero et al 2012). There are three earlier papers on delta Scuti stars, but they are actually misidentifications, and refer to DY Peg (HD 218549) and not to HIP 114328 (HD 218544).…”
Section: Discussionmentioning
confidence: 99%
“…Using the radii and v sin i measurements from Maldonado et al (2017) combined with our rotation period determinations it is possible to estimate the inclination of the star's pole to the line A89, page 9 of 17 of sight. Even for those stars where the period could not be determined from the time series, we have an estimation based on the mean level of chromospheric activity (Table A.3) in a similar way as in Herrero et al (2012). The parameters and uncertainties are calculated by bootstrapping simulations.…”
Section: Inclination Of the Star's Pole To The Line Of Sightmentioning
confidence: 99%